Analysis of the Grant Expenditure Budgetting Process in the Cianjur Regency APBD - Pusphita, Euis Erna (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the grant budgeting process in the Cianjur Regency Regional Budget (APBD), emphasizing the planning stage, allocation determination, and transparency and accountability mechanisms. The main focus of the study is directed at revealing the gap between the regulatory framework for grant expenditure management and the empirical practices that occur in the dynamics of regional budgeting. This study uses a qualitative approach with a case study design. Data were obtained through analysis of regional planning and budgeting documents, observations of official regional government information channels, and in-depth interviews with regional financial management officials and civil society representatives. Data analysis techniques were conducted thematically by linking empirical findings to the perspectives of incremental budgeting, political budgeting, and the principles of good governance. The results show that grant expenditure planning is still dominated by an incremental budgeting pattern with minimal performance evaluation, allocation determination is influenced by the dynamics of budget politics between executive and legislative actors, and transparency and accountability in grant management have not been optimal. Although regional regulations have regulated grant management in detail, their implementation tends to be administrative-formalistic and not fully oriented towards public needs and policy effectiveness. These findings imply that grant expenditure management reform cannot be achieved simply by improving administrative regulations, but requires strengthening performance-based planning capacity, limiting political discretion in budget forums, and developing participatory transparency and public oversight mechanisms.